Membangun Politik Desa yang Berbasis Kearifan Lokal di Desa Medan Estate - Julia Ivanna; Santiana Siboro (Universitas 17 Agustus 1945 Semarang, 2024)
Rural areas are defined as rural communities who live at the local level or what is known as a village. The dynamics of political life at the village level are very important to see and observe, because building an independent, advanced country and maintaining national integrity starts from the lowest level, namely the village or rural community. So awareness of the importance of developing rural communities continues until the current government, this is marked by the program run by the Central Government by providing fresh funds every year to villages throughout Indonesia. The village head election system cannot be separated from the dynamics in local political developments at the village level. In the village head election, there was a struggle for power, as is common in every round of Village Head elections in Indonesia. Candidates for village head use various methods in the village head election process in order to win the election and gain power at the lower level. Awareness of the importance of developing rural communities continues until the current government, this is marked by the program run by the Central Government by providing fresh funds every year to villages throughout Indonesia, of course this is an indication of the importance of developing communities at the village level so that they are independent and have higher productivity and will further improve the welfare of society. A village or rural environment (rural area) is a community that is always associated with simplicity, backwardness, traditionalism, subsistence and isolation (Rahardj, 1999)